Targeting Histone Modifications in Breast Cancer: A Precise Weapon on the Way - Li, Wei; Wu, Hao; Sui, Shiyao; Wang, Qin; Xu, Shouping; Pang, Da (Frontiers in Cell and Developmental Biology, 2021)
Histone modifications (HMs) contribute to maintaining genomic stability, transcription, DNA repair, and modulating chromatin in cancer cells. Furthermore, HMs are dynamic and reversible processes that involve interactions between numerous enzymes and molecular components. Aberrant HMs are strongly associated with tumorigenesis and progression of breast cancer (BC), although the specific mechanisms are not completely understood. Moreover, there is no comprehensive overview of abnormal HMs in BC, and BC therapies that target HMs are still in their infancy. Therefore, this review summarizes the existing evidence regarding HMs that are involved in BC and the potential mechanisms that are related to aberrant HMs. Moreover, this review examines the currently available agents and approved drugs that have been tested in pre-clinical and clinical studies to evaluate their effects on HMs. Finally, this review covers the barriers to the clinical application of therapies that target HMs, and possible strategies that could help overcome these barriers and accelerate the use of these therapies to cure patients.